2020
DOI: 10.3390/s20215993
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of IMU Sensor Placement for the Measurement of Lower Limb Joint Kinematics

Abstract: There is an increased interest in using wearable inertial measurement units (IMUs) in clinical contexts for the diagnosis and rehabilitation of gait pathologies. Despite this interest, there is a lack of research regarding optimal sensor placement when measuring joint kinematics and few studies which examine functionally relevant motions other than straight level walking. The goal of this clinical measurement research study was to investigate how the location of IMU sensors on the lower body impact the accurac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 38 publications
5
33
1
Order By: Relevance
“…Each participant was prepared for the experiment by securely placing sensors at each location on the right leg (see Figure 1). Although other locations on the upper thigh and lower torso were identified as common locations for IMU sensors in previous work [23], Panebianco et al found that torso-based algorithms generally performed worse than shank-or footbased algorithms [2], so only shank and foot locations were selected for investigation in this study. Additionally, very few studies report on thigh-based algorithms.…”
Section: Data Acquisitionmentioning
confidence: 94%
See 1 more Smart Citation
“…Each participant was prepared for the experiment by securely placing sensors at each location on the right leg (see Figure 1). Although other locations on the upper thigh and lower torso were identified as common locations for IMU sensors in previous work [23], Panebianco et al found that torso-based algorithms generally performed worse than shank-or footbased algorithms [2], so only shank and foot locations were selected for investigation in this study. Additionally, very few studies report on thigh-based algorithms.…”
Section: Data Acquisitionmentioning
confidence: 94%
“…A sensor-to-body calibration was used to transform IMU data into data in terms of the anterior-posterior (AP), medial-lateral (ML), and superior-inferior (SI) anatomical directions. The calibration approach used here has been previously described [23,41]. Briefly, this approach utilizes two static poses to determine the direction of anatomical axes using gravitational acceleration.…”
Section: Sensor Calibrationmentioning
confidence: 99%
“…The kinematic differences between the Opti_knee gait system and biplanar fluoroscopy system were quantified based on root mean square error (RMSE) [ 20 ] using Microsoft Office Excel (2013 version, Microsoft, Redmond, WA, USA). Bivariate Pearson correlations were calculated to compare the similarity trends between the two techniques using SPSS version 22.0 (IBM Corp., Armonk, NY, USA).…”
Section: Methodsmentioning
confidence: 99%
“…This is why gait analysis is constantly being actively studied. Marker-based optical motion capture (MoCap) systems are considered a gold standard in biomechanical gait research due to their high accuracy [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. In MoCap-based gait analysis, markers are attached to the lower limb of subjects and the gait is analyzed using the trajectories of these markers.…”
Section: Introductionmentioning
confidence: 99%